2020
DOI: 10.1097/nmd.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

“We're Afraid to Say Suicide”

Abstract: Suicide is a significant public health concern for veterans residing in rural communities. Although various initiatives have been implemented to prevent suicide among veterans, efforts specific to rural veterans remain limited. To aid such efforts, we examined stigma as a potential barrier to community readiness in the implementation of a community-based suicide prevention program for rural veterans. In this qualitative study, community readiness interviews were conducted with 13 participants in a rural commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 38 publications
0
15
0
2
Order By: Relevance
“…Interestingly, Steward et al [21] demonstrated that when controlling for level of education, employment, and income, older adults in rural counties were more likely to have elevated levels of public and self-stigma and less tolerance of psychological openness when compared to their urban counterparts. In another study by Monteith et al [22], the relationship between stigmas towards suicide and suicide rate for veterans in rural communities was explored. After surveying individuals, results demonstrated that suicide related stigma may in fact be one of the most important things to prioritize in deconstructing as a community-based suicide prevention program in rural communities to decrease suicide rates in veterans in rural counties [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Steward et al [21] demonstrated that when controlling for level of education, employment, and income, older adults in rural counties were more likely to have elevated levels of public and self-stigma and less tolerance of psychological openness when compared to their urban counterparts. In another study by Monteith et al [22], the relationship between stigmas towards suicide and suicide rate for veterans in rural communities was explored. After surveying individuals, results demonstrated that suicide related stigma may in fact be one of the most important things to prioritize in deconstructing as a community-based suicide prevention program in rural communities to decrease suicide rates in veterans in rural counties [22].…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Monteith et al [22], the relationship between stigmas towards suicide and suicide rate for veterans in rural communities was explored. After surveying individuals, results demonstrated that suicide related stigma may in fact be one of the most important things to prioritize in deconstructing as a community-based suicide prevention program in rural communities to decrease suicide rates in veterans in rural counties [22]. This speaks to the potential downfalls of many suicide prevention constructs in place today which rely heavily on technology and access to either said technology or those who possess it.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] This may disproportionately affect individuals in rural communities, who already experience increased stigma regarding mental health, suicide, and help-seeking. [50][51][52] Furthermore, due to existing shortages of mental health providers in rural communities, many individuals in rural areas rely upon primary care providers to provide mental health screening, resources, and treatment. [53][54][55] However, concerns about infection and triaging the most medically severe patients during the COVID-19 outbreak may further strain primary care providers' ability to provide such services.…”
Section: Mental Health and Access To Carementioning
confidence: 99%
“…The public stigma of suicide is thought to cause social distancing, or avoidance, towards those who attempt suicide (Corrigan et al 2017a;Lester 1993). As a result, public stigma can be a barrier to gatekeeping (Burnette et al 2015), including difficulties with saying the word "suicide" (Monteith et al 2020). The (World Health Organization (n.d.) has recognized that one myth of suicide is that "someone who is suicidal is determined to die".…”
Section: Effects Of Stigma On People With Suicidal Ideation or Behaviormentioning
confidence: 99%